Garbage Management: An Important Risk Factor for HPAI-Virus Infection in Commercial Poultry Flocks - Walz, Emily; Linskens, Eric; Umber, Jamie; Culhane, Marie Rene; Halvorson, David; Contadini, Francesca; Cardona, Carol (Frontiers in Veterinary Science, 2018)
Garbage management represents a potential pathway of HPAI-virus infection for commercial poultry operations as multiple poultry premises may share a common trash collection service provider, trash collection site (e.g., shared dumpster for multiple premises) or disposal site (e.g., landfill). The types of potentially infectious or contaminated material disposed of in the garbage has not been previously described, but is suspected to vary by poultry industry sector. A survey of representatives from the broiler, turkey, and layer sectors in the United States revealed that many potentially contaminated or infectious items are routinely disposed of in the trash on commercial poultry premises. On-farm garbage management practices, along with trash hauling and disposal practices are thus key components that must be considered in order to evaluate the risk of commercial poultry becoming infected with HPAI-virus.